Edukasi Gerakan Masyarakat Hidup Sehat (Germas) sebagai Upaya Mencapai Kualitas Kebugaran Lanjut Usia - Atikah Rahayu Firmansyah; Widiyanto Widiyanto; Eka Swasta Budayati (Universitas Baiturrahim, 2026)
Elderly people are one group of people who need attention from their environment. Good fitness quality can be achieved by implementing physical activity for at least 150 minutes per week, consuming fruit and vegetables, checking your health regularly. This component is part of the Healthy Living Community Movement (germas). The importance of this Germas component is because data on physical activity in the underweight category has increased by 7% (aged 60-64), underconsumption of vegetables and fruit has increased by 9.6%, and routine check-ups are not yet optimal as can be seen from the morbidity rate. Community Service Method: socialization with material presentations, discussions, demonstrations and mentoring of 34 elderly people carried out on Thursday, 26 June 2025 at the Main Building of the Tempel Unit Village Community Empowerment Institution, Besalen Hamlet, Baturetno Village, Banguntapan District, Bantul Special Region of Yogyakarta. The activity design is divided into 3 stages (Preparation, Implementation and Evaluation). Results: Program implementation > 50% or 2/3 of the invitation list attended, and all participated actively by asking questions related to educational material. Conclusion: The great desire of the elderly to gain knowledge related to germs to improve fitness, so it is necessary to continue carrying out the same activities again with broader material